Angularis oris axial pattern flap as a reliable and versatile option for rostral facial reconstruction in cats - Albernaz, Vinicius G. P. [UNESP]; Oblak, Michelle L.; Quitzan, Juliany G. [UNESP] (Wiley, 2021)
Objective: To evaluate outcomes associated with the use of an angularis oris axial pattern flap (AOAPF) for rostral facial reconstruction in cats. Animals: Nine adult client-owned cats. Study Design: Short case series. Methods: Ten AOAPF were performed in nine cats after resection of a tumor. Wounds were located at the nose, infraorbital, supraorbital, frontal, eye, and ear canal region. Orbital exenteration (n = 3), pinnectomy (n = 2), nasal planum resection, total ear canal ablation (n = 2), and partial eyelid reconstruction (n = 3) were performed. Results: Short-term postoperative complications included flap edema (n = 10), suture dehiscence (n = 3), and distal tip necrosis (n = 3). All wounds resulting from minor complications healed by second intention in 5–15 days. Long-term complications included epiphora (n = 2), frequent grooming around the eyes (n = 2), and enucleation due to corneal ulcer secondary to impaired postoperative eyelid function (n = 1). Tumor recurrence occurred in 3 cases. Conclusion: The AOAPF was a versatile and reliable option for rostral facial reconstruction in cats with acceptable long-term outcomes.